Pengaruh Pemberian Rendam Kaki Air Hangat Terhadap Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Tigo Baleh Kota Bukittinggi - Habib Bullah; Sisca Oktarini; Yuli Permata Sari (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The high prevalence of hypertension is one of the problems that affect the health status of the community. lifestyle changes, age, gender, and factors that encourage the onset of hypertension. To prevent hypertension from causing further complications, appropriate and efficient treatment is needed, the treatment of hypertension in general is pharmacological. The management of hypertension can use non-pharmacological therapy by soaking the feet in warm water. The purpose of this study was to determine the difference before and after giving a foot soak using warm water to the degree of blood pressure in hypertensive patients in the Working Area of the Tigo Baleh Health Center, Bukittinggi City. This study used a sample of 10 respondents with an experimental design one group times series design, namely checking blood pressure before and after giving a warm water foot soak. The data processing technique uses SPSS 16 with data analysis using the Paired T-Test. The results of the study found that the mean pre- test (3.40) and post-test (2.30) were the results of the Paired T-Test and obtained a value of p <0.05, which is 0.00, meaning that there is an influence between blood pressure before and after given a warm water foot soak. From the results of this study, soaking feet using warm water on a decrease in blood pressure has an effect on hypertension sufferers in the Working Area of the Tigo Baleh Health Center, Bukittinggi City. Thus, soaking feet in warm water can be used as a non- pharmacological method of lowering blood pressure in sufferers